Reconstructing Fiqh Muamalah for the Digital Age : A Framework for Shariah-Tech Integration - Mansur, Mansur; Assulthoni, Fahmi; Nikmah, Fathiyatun; Masithoh, Fitria Nur (Journal of Islamic Economics Studies and Practices, 2025)
Fiqh Muamalah Iqtishadiyah, as the legal framework for Islamic economics, faces transformative challenges amidst the rapid development of the digital financial landscape. This article aims to provide a critical review of the classical paradigm of Fiqh Muamalah Iqtishadiyah and identify opportunities and challenges for its integration into contemporary digital financial systems. Employing a descriptive-analytical qualitative approach and an in-depth literature study, this research analyses the gap between the theoretical constructions of traditional fiqh muamalah and the operational demands of the digital economy, including Shariah fintech, cryptocurrency, smart contracts, and digital-based funding platforms. The study's findings indicate that while fundamental principles such as al-'uqud (contracts), the prohibition of riba (usury), gharar (excessive uncertainty), and maysir (gambling) remain relevant, the classical paradigm faces limitations concerning contract mechanisms, transaction oversight, and consumer protection in the digital ecosystem. On the other hand, significant opportunities for integration are found through the reinterpretation (ilhaq) of the concept of 'urf (custom), the strengthening of digital Shariah standards (Shariah Compliance Tech), and the development of hybrid models that accommodate blockchain and artificial intelligence. This article concludes that the transformation of Fiqh Muamalah Iqtishadiyah is not only necessary but inevitable, proposing an evolutionary framework that combines the resilience of normative Islamic values and the flexibility of technological adaptation. The implications of this study provide direction for regulators, academics, and practitioners in designing a robust, inclusive, and competitive Islamic financial architecture for the digital era.